Energy Efficiency Improvement Method for Storage-type Hot and Cold Water Dispenser Based on Structure of Multi-layer Water Separator - Wang Yueming; Lu Jingchao; Zhuang Dawei; Ding Guoliang; Zheng Yuedong; Han Cong; Wang Congcong (Zhileng xuebao)
This study proposes a novel method to improve the cold water supply capacity and reduce energy consumption using a multi-layer water separator to replace the single-layer water separator. This method can delay the mixing intensity between ambient temperature water and cold water and increase the average temperature under the standby state inside the cold tank. The relationship between the structural parameters of the multi-layer water separator, cold water temperature, and cold water volume in each layer is established, and an optimization method for the structural parameters is proposed. An optimized design example is given using a multi-level separator to replace the single-layer water separator in the storage hot and cold water dispenser, and an experiment is conducted. The experimental results prove that the standby energy consumption of the water dispenser fabricated using the newly proposed three-layer water separator is reduced by 15% with the same release capacity when compared with the baseline structure.